Consumo e violência no funk proibidão - Perestrelo, João Rodrigo Rocha (2017)
The goal of this work is to understand how the Zizek (2014) subjective violence is conveyed in messages inserted in the lyrics of the “Funk Proibidão”. Aiming to stablish such enunciative functions related to violence inserted on the lyrics, as a start point, the following question must be answered: “With which enunciative functions objects related to subjective violence are shown on the FUNK Proibidao? ”. 18 songs, of the same kind, were selected from YouTube, channel “O Coringa Vida Loka” and analyzed individually. The result of this analysis helped us to attain our goal. It pointed out that different brands and classes of products present in their lyrics are used to: ( i ) Declare the existing union among groups; ( ii ) As a way for a group/individual to self-assert; ( iii ) To describe the status of a group/individual; ( iv ) To convey a warning; and ( v ) To describe the conditions that lead a group/individual to do something.